(untitled) (Journal of Partial Differential Equations, 2020)
In this paper, we will consider the degenerate nonlinear boundary value problems for nonlinear elliptic equations. We extend Lieberman & Trudinger’s results from nondegenerate oblique derivative boundary values to degenerate boundary values.